Hypochlorous acid reversibly inhibits caspase-3: a potential regulator of apoptosis. (2nd January 2020) - Jeelani, Roohi; Chatzicharalampous, Charalampos; Kohan-Ghadr, Hamid-Reza; Bai, David; Morris, Robert T.; Sliskovic, Inga; Awonuga, Awoniyi; Abu-Soud, Husam M.
Abstract: Caspase-3 is involved in apoptosis. Here, we examine whether hypochlorous acid (HOCl), a final product of myeloperoxidase (MPO), is a modulator of caspase-3 at relatively low concentrations and also its application on metaphase II mouse oocytes. We utilised caspase-3 activity assay, TUNEL assay, the CellEvent caspase 3/7 fluorescent assay, and the MPO/hydrogen peroxide (H2 O2 ) system on mouse oocytes with and without cumulus cells to examine whether low concentrations of HOCl mediate apoptosis by inhibition of caspase-3. A UV-visible spectrophotometer was used to study caspase-3 activity. To determine whether HOCl mediates apoptosis in mouse oocytes, two different concentrations (10 and 100 µM) of HOCl generated by the MPO/H2 O2 system were used as treatments (10 µM had little effect on oocyte quality, while 100 µM showed significant deterioration). Induction of apoptotic cell death was determined by TUNEL Assay and the CellEvent caspase 3/7. HOCl mediates caspase-3 inactivation in a dose dependent manner. Subsequent addition of dithiothreitol caused recovery of caspase-3 activity indicating involvement of the oxidation of the Cys-thiol group. Accumulation of HOCl generated by MPO in the presence of caspase-3 also inhibits MPO but requires higher HOCl concentrations, indicating specificity of lower HOCl concentrations to inhibition of caspase-3. Exposure of oocytes to lower HOCl concentrations generated by MPO-H2 O2 system prevents MPO-mediated apoptosis whereas exposure to higher HOCl (100 µM) showed apoptosis. Similar results were observed by using the CellEvent caspase 3/7 assay. Low concentrations of HOCl inhibit caspase-3 activity, and may play a role in regulating apoptosis, thus affecting oocyte quality. Highlights: Caspase-3 is involved in apoptosis pathway and loss of this regulation is seen in several diseases. These conditions are associated with inflammation and higher myeloperoxidase (MPO) activity. We examined whether hypochlorous acid (HOCl), generated by MPO, is a modulator of caspase-3. Caspase-3 activity showed a dose dependent decrease with HOCl and this reaction was reversible. HOCl modulates caspase-3 activity and may play a physiological role in regulating apoptosis.